(untitled) (Medical Forum Monthly, 2023)
Objective: Study was designed to assess the knowledge, skill and attitude of community midwives before and after three days training workshop on the subject insertion of intrauterine device, as a tool for family planning. Study Design: Observational / descriptive study. Place and Duration of Study: This study was conducted at Community Medicine, Sharif Medical & Dental College, Jati Umra, Lahore and Department of Public Health, The University of Lahore from January 2015 to June 2015 Materials and Methods: An intervention study was conducted by collecting data from designing structured questionnaire which was answered by the midwives taking part in the training to evaluate their basic knowledge, skill and attitude towards use of intrauterine devices. This study was based on three phases. 1) assessment 2) intervention 3) evaluation. Thirty community midwives in the community based maternity homes of Lahore was selected as subjects. Data through a pretested questionnaire was collected and analyzed by statistical package for social sciences (SPSS). Results: 50-70% of community midwives had the basic knowledge of IUD, insertion skill and its benefits, before going through the training. After the training, knowledge of IUD, its insertion skill and advice to women increased up to 85-100% among the participants. Results clearly show that the knowledge of the community midwives regarding use of IUDs use as a family planning tool was minimal and increased after getting the training. Conclusion: Study finding suggested that training is essential for the community midwives for improving their knowledge, technical skill for insertion of IUD, and aptitude for counseling to the families upon follow up visits.